(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Enterostomal therapist is just one of the titles used globally to identify nurses trained in the specialty of ostomy, wound and continence nursing (OWC). Enterostomal therapy involves components of expert clinical practice, education, leadership and research. Enterostomal therapists(ETs) are entrusted to be accountable for using their expertise to provide consultation for patients, physicians, nurses, health care organisations and the public.